PANDANGAN HAMKA (HAJI ABDUL MALIK ABDUL KARIM AMRULLAH) TAHUN 1908-1981: Konsep Pembangunan Ekonomi - Ihwanudin, Nandang (Moderation | Journal of Islamic Studies Review, 2021)
Abstract: Hamka presented the idea of ​​an ideal economy, namely an economy of prosperity that is built on the principle of faith so as to give birth to social welfare. He criticized the capitalist economy, which according to Schumpeter, with this economic system, economic development would be rapid. According to him, the economic system has failed by creating a wide gap between the rich and the poor. In this study, the authors are interested in examining more deeply the objectives of economic development, the economic system, and the idea of ​​economic development in Hamka's view by using a descriptive analysis method of analysis of Hamka's works and presented through a qualitative approach. The findings in this study are: 1) the economic objectives according to Hamka are for the prosperity of individuals and society in the form of social justice based on faith and in line with ethical values; 2) Hamka criticizes the capitalist economic system as an economic system that has failed in developing the economy because increasing prosperity does not bring about social welfare, but creates economic disparities between the rich who own capital and the increasingly poor workers. Hamka also criticized the socialist economic system which only gave birth to an even distribution of poverty and gave birth to a new bourgeoisie; 3) Hamka offers the idea of ​​economic development based on the values ​​of justice, willingness, liberation, innovation, high creativity, cooperation, avoiding illegal, vanity, corruption, and usury economic activities. He also gave the idea of ​​establishing a bank without usury and promoting philanthropy in the form of zakat, donations and alms. There are differences between Hamka's thoughts on economic development and Schumpeter's in terms of an ideal economic system and there are similarities in the maximum use of natural resources, among others, through innovation.